2004
DOI: 10.1073/pnas.0405496101
|View full text |Cite
|
Sign up to set email alerts
|

Bbs2 -null mice have neurosensory deficits, a defect in social dominance, and retinopathy associated with mislocalization of rhodopsin

Abstract: Bardet-Biedl syndrome (BBS) is a heterogeneous, pleiotropic human disorder characterized by obesity, retinopathy, polydactyly, renal and cardiac malformations, learning disabilities, hypogenitalism, and an increased incidence of diabetes and hypertension. No information is available regarding the specific function of BBS2. We show that mice lacking Bbs2 gene expression have major components of the human phenotype, including obesity and retinopathy. In addition, these mice have phenotypes associated with cilia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
380
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 349 publications
(421 citation statements)
references
References 28 publications
32
380
2
3
Order By: Relevance
“…Second, there are three relevant knockout mouse models for genes within the linked interval: Pappa (31), Astn1 (paralogue of Astn2) (32), and Tlr4 (33). These models do not have phenotypes that resemble BBS mouse models (34)(35)(36). Finally, functional characterization of other TRIM proteins indicates involvement with components of the cytoskeleton, a finding consistent with the function of other BBS proteins (37)(38)(39).…”
Section: Discussionsupporting
confidence: 56%
“…Second, there are three relevant knockout mouse models for genes within the linked interval: Pappa (31), Astn1 (paralogue of Astn2) (32), and Tlr4 (33). These models do not have phenotypes that resemble BBS mouse models (34)(35)(36). Finally, functional characterization of other TRIM proteins indicates involvement with components of the cytoskeleton, a finding consistent with the function of other BBS proteins (37)(38)(39).…”
Section: Discussionsupporting
confidence: 56%
“…The phenotypes of the MKKS-knockout mouse (Fath et al, 2005) closely resemble those of mice disrupted for the BBS1, BBS2, or BBS4 genes (Kulaga et al, 2004;Nishimura et al, 2004), and many of these phenotypes have been suggested to be caused by ciliary dysfunction. In the case of the BBS2-knockout mouse, the photoreceptor degeneration is preceded by mislocalization of rhodopsin, which indicates a defect in protein transport.…”
Section: Discussionmentioning
confidence: 94%
“…53 Rod-cone dystrophy is thought to be a consequence of abnormal trafficking across the defective modified cilia connecting the inner and outer segments of photoreceptors leading to apoptosis. 50,54,55 Receptors for sonic hedgehog signalling are found on cilia in the developing limb buds. 55 IFT proteins are thought to modulate this pathway 39 and dysregulation has been associated with the limb malformations observed in ciliopathies.…”
Section: Biology Of the Diseasementioning
confidence: 99%